DEVELOPING ENGLISH LANGUAGE TEACHERS’ PROFESSIONAL AND METHODOLOGICAL PREPAREDNESS FOR IMPLEMENTING DIFFERENTIATED INSTRUCTION IN HIGHER EDUCATION - Akbarova Umidakhon (International Journal of Literature and Language Studies, 2026)
This article provides a theoretical and analytical discussion of developing English language teachers’ professional and methodological preparedness for the effective implementation of differentiated instruction in higher education institutions. English language groups in higher education often have the characteristics of mixed-ability classrooms, where students differ in terms of language proficiency, academic preparedness, learning needs, motivation, and communicative abilities. In such conditions, differentiated instruction is regarded as an important approach that enables English language lessons to be adapted to students’ actual needs. However, the effective implementation of this approach requires not only theoretical knowledge but also a set of professional and methodological competencies, including diagnostic assessment, flexible lesson design, differentiated assessment, individualized feedback, the use of digital resources, and reflective practice. The article analyzes the role of teacher preparedness in implementing differentiated instruction based on the views of Ahearn, Benothmane, Little, Massey, Morrison-Shuford, Cressman, Ali, Van Petten, and other researchers. The scientific and methodological novelty of the article lies in the proposal of a five-stage professional and methodological model for developing English language teachers’ preparedness for differentiated instruction in higher education. This model includes diagnostic assessment, needs-based professional development, methodological coaching, professional learning communities, and reflective redesign. The proposed model can support English language teachers in implementing differentiated instruction systematically, consciously, and methodologically in their teaching practice.